Use of membranes for the treatment and reuse of water from the pre-cooling system of chicken carcasses - Marchesi, Cristiane M (Environmental technology, 2021)
Poultry processing plants generate large amounts of wastewater in the many steps necessary to provide high quality and safe products. Carcass chilling is one of these steps, where the temperature of the carcass is reduced from 40°C to 4°C, for reducing the growth rate of microorganisms and affecting flavour, texture and appearance. In this operation, carcasses are continually displaced through a series of two tanks (called pre-chiller and chiller) filled with cold water, thus being responsible for a considerable amount of wastewater generation. This work aimed to regenerate the wastewater of the pre-chiller tank employing microfiltration (pore size 0.10 and 0.20 µm) and ultrafiltration (UF; MWCO 10 and 50 kDa) polymeric membranes in bench and pilot scales, with the final purpose of reuse. Membrane performance was evaluated in terms of the capacity of removing the contaminants and producing sufficient permeate flux in different working pressures. Bench-scale UF membrane presented the highest initial permeate flux of 112.1 L/m2h at 200 kPa. The four membranes tested presented good retention of microorganisms, with apparent rejection of up to 100%. Pilot-scale membranes presented better apparent rejection, with retentions above 99% for turbidity, apparent colour and fat content. Moreover, organic matter retention was also very high, up to 94% for chemical oxygen demand and 92% for total organic carbon. The use of membranes seems to be a promising approach for recycling and reuse of poultry pre-chiller wastewater